PENGUKURAN KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA BMT SYARIAH AR RAHMAH KABUPATEN SUKOHARJO - Muhammad Hiksa Reisfansyah; Ari Pradhanawati (Universitas Diponegoro, 2017)
The business sector that is being highlighted by its development is Micro, Small and Medium Enterprises (UMKM). It is a cooperative institution as a micro finance institution that actively participates in the effort to enhance the quality of community life, one of which is implemented by helping UMKM from capital or financing side. Sharia Financial Services Cooperative (KJKS) or the term commonly called Baitul Maal wa Tamwil (BMT) is a cooperative whose business activities are engaged in financing, investment, and savings in accordance with the pattern of profit sharing (syariah) based on the principle of kinship.This type of research is case study with data collection method by designating key informant from BMT. The Object in this study BMT Syariah Ar Rahmah by measuring its performance with balanced scorecard method consisting of 4 perspectives namely, financial perspective, customer perspective, internal business perspective and learning and growth perspective.Based on the results of the research shows that the customer perspective has the lowest score compared to 3 other perspectives. This shows the gap between the realization with the target that has been declared. Based on this study concluded that the performance of BMT with balanced scorecard get score 123.86 including having a healthy performance because it exceeds the upper limit of score classification.However, there is a gap in the perspective of customer perspective scores with other perspectives with a score of only 6.61 which includes a very not healthy, researchers recommend BMT to pay attention to more factors member that is collecting a lot of members each year and retain existing members